Response of cowpea [Vigna unguiculata (L) Walp] to residual effect of different application rates of sheep manure on chilli pepper (Capsicum annuum) - Babaji, B.A.; Yahaya, R.A.; Mahadi, M.A.; Jaliya, M.M.; Ajeigbe, Hakeem A.; Sharifai, A.I.; Kura, H.N.; Arunah, O.L.; Ibrahim, A. (2010)
Field experiments were conducted in 2005 and 2006 rainy season at the Institute for Agricultural Research farm, Samaru, Nigeria, to test the response of four cowpea [Vigna unguiculata (L) Walp] varieties to residual effect of four rates of sheep manure (FYM) (0, 5, 10 and 15 t/ha) applied the previous season to chilli pepper [Capsicum annuum]. Each of the experiment was a follow up to a previous one conducted in 2004 and 2005 to test the response of pepper to those rates of FYM. Applications of different rate of FYM had significant residual effect on soil chemical content. The combined results showed significant difference among the cowpea varieties for grain yield and yield components. Mean cowpea grain yield ranged from 1.7 t/ha in IT96D-757 to 2.7 t/ha in IT97K-499-35. Previous FYM application rate significantly affected cowpea grain yield, pod weight, number of seeds per pod, seed weight per pod and threshing percentage. However, 100-seed weight was not significantly affected. Cowpea grain yield ranged from 1.4 t/ha in plots without FYM to 2.4 t/ha in plots that had 10 or 15 t/ha previous year. Significant interaction was not observed between cowpea variety and previous manure application rate.